Pendidikan Karakter Islami dalam Novel “Tentang Kamu” - Gofarun Gofarun; Abdul Munif (Tadrisuna : Jurnal Pendidikan Islam dan Kajian Keislaman, 2024)
Today's character education shows a decline in student character. This is due to the rapid advancement of technology and the absence of comprehensive character education using new methods. This study aims to analyze and reveal the values ​​of character education contained in the novel "About You." The research problem formulation raised is how is Islamic character education illustrated in the novel "About You?" The research method used in this study is qualitative descriptive, and also uses the content analysis method. The results of the study show many illustrations of Islamic character education contained in the novel "About You," such as the honest/integrity character shown by Sri Ningsih. In addition to good characters, there are also bad characters illustrated in the novel, such as Sulastri with her cunning and insidious character. In this study, we hope that this can make a positive contribution to Islamic character education.